Cosmetics and Personal Care Products-Related Ocular Exposures Reported to United States Poison Control Centers. (3rd September 2022) - Kamboj, Alisha; Spiller, Henry A.; Funk, Alexandra R.; Badeti, Jaahnavi; Smith, Gary A.
ABSTRACT: Purpose: To study cosmetics and personal care products-related ocular exposures in the United States. Methods: A retrospective analysis of cosmetics and personal care products-related ocular exposures from 2000 through 2018 was conducted using data from the National Poison Data System. Results: From January 2000 through December 2018, United States Poison Control Centers received 266, 743 calls concerning eye exposures to cosmetics and personal care products, corresponding to a mean of 14, 039 calls per year. Young children (<6 years old) represented 51.6% of exposures, while older children and teenagers (6–19 years old) and adults (≥ 20 years old) represented 19.5% and 28.9% of exposures, respectively. Over the study period, the annual frequency of exposures decreased by 46.0%. The product subcategories associated with the highest proportion of exposures were perfumes, colognes, and aftershaves (19.0%), suntan and/or sunscreen products (11.2%), nail polishes (9.5%), soaps (6.3%), and creams, lotions, and make-up (5.8%). The product subcategories associated with the greatest proportion of moderate or major medical outcomes were acrylic nail adhesives (14.4%), miscellaneous nail products (12.9%), other hair care products excluding peroxides (10.9%), hair coloring agents excluding peroxides (8.9%), and peroxides (7.5%). Conclusions: Although the annual frequency of exposures to cosmetics and personal care products declined during the study period, public health efforts are needed to prevent further ocular exposures to these products. Containers of potentially ocular-toxic products should be redesigned to reduce confusion with eye dropper bottles and to reduce attractiveness to young children, with immediate priority placed on acrylic nail adhesives.